Participação do receptor de potencial transitório anquirina 1 e disfunção mitocondrial em um modelo de fibromialgia em camundongos - Brum, Evelyne da Silva (2022)
Fibromyalgia is a painful condition associated with several comorbidities. Although the mechanism underlying fibromyalgia remains unknown, monoamine depletion, reactive oxygen species (ROS) overproduction, and mitochondrial dysfunction appear relevant in its pathogenesis. Once Transient Receptor Potential Ankyrin 1 (TRPA1), an oxidative stress sensor, is involved in conditions related to the pathogenesis of fibromyalgia, including spontaneous and musculoskeletal pain, fatigue and depressive and anxiety behaviours, we hypothesized that TRPA1 could be involved with fibromyalgia symptoms. The fibromyalgia model was induced by subcutaneous injections of reserpine (1 mg/kg) once daily for three consecutive days in Swiss and C57BL/6J mice and in TRPA1-deficient mice. All behavioural tests were performed on the 4 th day after the first administration of reserpine. Immediately after, the animals were euthanized, and different tissues (gastrocnemius and soleus muscles, plantar tissue, sciatic nerve, and spinal cord) were collected for biochemical investigations. Coenzyme Q10 and oligomycin were used to assess mitochondrial function and characteristic symptoms of fibromyalgia. α-lipoic acid was used to elucidate the role of oxidative stress in the fibromyalgia model. The TRPA1 antagonist, A-967079, was used to assess TRPA1 involvement, while the pregabalin or duloxetine were used as reference drugs for fibromyalgia symptoms. Reserpine reduced monoamine levels, caused mechanical and cold allodynia, chemical hypersensitivity, reduced muscle strength and burrowing behaviour, caused thigmotaxic behaviour and increased the immobility time of animals in the forced swim test. Oligomycin exacerbated reserpine-induced fibromyalgia-like symptoms, while coenzyme Q10, α-lipoic acid, A-967079, pregabalin, and duloxetine attenuated different reserpine-induced nociceptive and comorbid parameters. Local administration of reserpine induced acute hypersensitivity. Reserpine induced mitochondrial dysfunction (high-resolution respirometry) and altered oxidative status (ROS levels and lipid peroxidation) in the soleus and gastrocnemius muscles and spinal cord. Reserpine increased H2O2 levels in the plantar tissue and increased staining for 4-hydroxynononeal in the sciatic nerve. These oxidative parameters and fibromyalgia-like painful symptoms were not observed when reserpine was administered in TRPA1-deficient mice. Thus, mitochondrial dysfunction and oxidative stress are essential mechanisms for TRPA1 activation and, therefore, for the development and maintenance of the hypersensitivity and some comorbidities observed in this fibromyalgia model. In this way, we contribute to advances in the mechanisms involved in the pathophysiology of fibromyalgia and encourage the use of possible new treatments to control the symptoms of this pathology.